2019
DOI: 10.1093/eurheartj/ehz453
|View full text |Cite
|
Sign up to set email alerts
|

Impact of long-term ticagrelor monotherapy following 1-month dual antiplatelet therapy in patients who underwent complex percutaneous coronary intervention: insights from the Global Leaders trial

Abstract: Aims  To evaluate the impact of an experimental strategy [23-month ticagrelor monotherapy following 1-month dual antiplatelet therapy (DAPT)] vs. a reference regimen (12-month aspirin monotherapy following 12-month DAPT) after complex percutaneous coronary intervention (PCI). Methods and results In the present post hoc analysis of the Global Leaders trial, the primary endpoint [composite of all-cause death or new Q-wave myoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
108
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 106 publications
(118 citation statements)
references
References 23 publications
7
108
1
2
Order By: Relevance
“…(3) Together these findings indicated that regardless of HBR, complex PCI was an independent driver of adverse ischemic outcomes without an excess of bleeding events, suggesting that the use of potent P2Y 12 inhibitors may be beneficial to patients who underwent complex percutaneous revascularization. We observed that PCI complexity exerted an adverse impact not only on MACE proportional to the number of complexity criteria present, but also on all individual endpoints including cardiac death, MI, definite/probable ST, and TLR, findings that corroborated results from previous reports [7][8][9][10][11][12]. Intriguingly, subjects with complex PCI did not experience a significant increased risk of clinically relevant bleeding, as compared with the noncomplex PCI group.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…(3) Together these findings indicated that regardless of HBR, complex PCI was an independent driver of adverse ischemic outcomes without an excess of bleeding events, suggesting that the use of potent P2Y 12 inhibitors may be beneficial to patients who underwent complex percutaneous revascularization. We observed that PCI complexity exerted an adverse impact not only on MACE proportional to the number of complexity criteria present, but also on all individual endpoints including cardiac death, MI, definite/probable ST, and TLR, findings that corroborated results from previous reports [7][8][9][10][11][12]. Intriguingly, subjects with complex PCI did not experience a significant increased risk of clinically relevant bleeding, as compared with the noncomplex PCI group.…”
Section: Discussionsupporting
confidence: 89%
“…Given the association of anatomical complexity and functional severity of CAD with future cardiovascular events [4,5], the concept of complex PCI and higher-risk indicated population for revascularization has recently been proposed [6,7]. However, there is no universal definition of complex PCI in terms of angiographic and lesion characteristics, in turn causing in a variety of clinical outcomes reported in previous studies [7][8][9][10][11][12]. Although procedural complexity emerges as a correlate of ischemic events, controversial results have been reported in many studies evaluating the adverse impact of complex PCI procedures on bleeding events [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The superiority of the experimental strategy at 2 years was not demonstrated in the parent trial. However, non-specified secondary analyses suggested the potential efficacy of this novel experimental regimen in some specific patient subgroups [12][13][14][15]. To unravel the complex intricacies of the GLOBAL LEADERS trial, the present study aims to investigate the clinical impact of BMI on the novel antiplatelet strategy with ticagrelor monotherapy in patients undergoing PCI.…”
Section: Introductionmentioning
confidence: 99%